Interfacial engineering of core/shell heterostructured nanocrystal quantum dots for light-emitting applications - Chang, J.H.; Hahm, D.; Char, K.; Bae, W.K. (한국정보디스플레이학회, 2017)
Reviewed in this paper is the recent progress on the interfacial engineering of core/shell heterostructured nanocrystal quantum dots (NQDs) for light-emitting applications, with focus on the composition (energy) gradient interfaces between the core and the shell. The engineered interfaces mitigate the structural stress between the core and the shell and thus reduce the chance to create misfit defects that act as efficient non-radiative recombination centers. In addition, the resultant smoothening of the potential profiles across the interfaces leads to the strong suppression of non-radiative Auger recombination. Efforts to engineer the interfacial structures further promote the optical performances of NQDs and benefit the light-emitting applications utilizing NQDs. ？ 2017 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.